Hello there.
In this problem, we can use our intuition of logic, but I will show a proof of the result in a truth table later. Then, let's get started!
Given:
→ Amelia finishes the homework (sentence H, can be True or False)
→ Amelia goes to the park (P, true or false)
Then, we have: If H, then P. Logically:
H ⇒ P
Then we can think: everytime she does the homework, she goes to the park. Therefore, if she did not go to the park, she will not have finished the homework (It is an equivalent sentence).
Alternative 1.
==========
Now, let's prove that (H ⇒P) is equivalent to (¬P ⇒ ¬H), via the truth table:
H P ¬H ¬P (H ⇒ P) (¬P ⇒ ¬H)
T T F F T T
T F F T F F
F T T F T T
F F T T T T
As we can see, the results are identical, therefore, the sentences are indeed equivalent.
I hope it hepls :)
How tall is Freddie's mother?
Answer:
0.25 1/2 of 1/2 is 0.25 sorry i just can't. studie peps. i want u to be this not this^﹏^
Step-by-step explanation:
-_--_--_--_--_-
To solve for x in a triangle with side lengths of 67, 29, and x, we can use the Law of Cosines. The value of x is approximately 47.6.
To solve for x in the given triangle with side lengths 67, 29, and x, we can use the Law of Cosines. The Law of Cosines states that for any triangle with side lengths a, b, and c and angle C opposite side c, the following equation holds true: c^2 = a^2 + b^2 - 2ab*cos(C). In this case, we can substitute the given values into the equation and solve for x. Let's calculate it:
x^2 = 67^2 + 29^2 - 2*67*29*cos(C)
x^2 = 4489 + 841 - 3886cos(C)
Solving for x, we find that x is approximately 47.6.
#SPJ12
Answer:
84°
Step-by-step explanation:
Because every triangle has a combined side length of 180°
67+29=96°
180-96=84°
Answer:
k=4/3
Step-by-step explanation:
5(2k-1)-k=7
10k-5-k=7
9k=12
k=4/3
Answer:
D
Step-by-step explanation:
For simplify the work we can start to factorise all the possibles expressions:
2x + 8.
8 is multiple of 2, so it can became
2(x+4)
x^2 - 16 this is a difference of two squares, so it can be rewritten as:
(x+4)(x-4)
x^2 + 8x + 16
we have to find two numbers whose sum is 8 and whose product is 16
the two number are 4 and 4
it becames:
(x+4)(x+4)
x+ 4 can‘t be simplified
if we look at the expression, we can find that x-4 appears at the numerator so
x^2 - 16 must be at numerator
but the second factor (x+4) doesn’t appear, so has been simplified. This situation can be possible only in the D option
in fact
(x+4)(x-4)/2(x+4) * (x+4)/(x+4)(x+4)
it became
(x+4)(x-4)/2 * 1/(x+4)(x+4)
(x-4)/2(x+4)
Answer:
Step-by-step explanation:
I got 100% on the test